Is there a relationship between creativity and stylistic preference in a group of nursing students? - Almansa Martínez, Pilar; López Martínez, Olivia (Anales de Psicología / Annals of Psychology, 2010)
The general mission of this work is to see that relation exists between the thinking styles and the creativity in students of the nurse school. The used total sample is of 78 students, pertaining to the Nurse School of the University of Murcia (Spain). The students belong to the courses of 1º and of 3º and the applied tests have been the Thinking Styles Inventory of Sternberg and Wagner and the Test of Creative Intelligence (CREA) of Corbalán and collaborators.